Thermal properties of biomass tar at rapid heating rates - Huan, Zhang; Kun, Zhang; Xuehua, Zhou; Jianjun, Hu; Yanyan, Jing; Shengyong, Liu (International Journal of Agricultural and Biological Engineering, 2014)
Gasification of biomass tar by pyrolysis is a valuable source for renewable energy, providing chemicals, a precursor to carbon material and potentially a raw material for liquid fuel. In this research, experimental studies via thermal gravimetric analysis (TGA) of biomass tar were implemented at three rapid heating rates (i.e., 10 K/min, 50 K/min, 100 K/min, respectively) in a nitrogen atmosphere. On the basis of analytical methods utilized in thermal dynamics and physical chemistry, the results showed that the thermogravimetric curve (TG) of the biomass moved in a high-temperature direction with an increase in the heating rate. The greater the heating rate, the steeper the curve and the lower the resolution, the lag phenomenon of the temperature being more significant. Concurrently, a differential thermal analysis (DTA) was one of the methods employed to study the relationship between the temperature difference and the temperature or time of the tested substance and a reference substance. The peak temperature and maximum reaction rate of the differential thermal analysis curve (DTA) increased as the heating rate, the volatiles and the molecular residence time of the biomass was shortened at a higher heating rate, thereby potentially inhibiting the generation of carbon and increasing the production and yield of liquid fuel. Keywords: biomass tar, liquid fuel, rapid heating rate, thermal dynamics, pyrolysis, gasification, renewable energy DOI: 10.3965/j.ijabe.20140702.012 Citation: Zhang H, Zhang K, Zhou X H, Hu J J, Jing Y Y, Liu S Y. Thermal properties of biomass tar at rapid heating rates. Int J Agric & Biol Eng, 2014; 7(2): 101－107.